Exploring the prevalence of gout among underrepresented low socioeconomic status type 2 diabetes populations - Jessica Smith; Abey Martin; Jane Mundadan; Michael Roberts; Youssef Roman; Arturo Bravo-Nuevo; Farzaneh Daghigh (Diabetology & Metabolic Syndrome)
Abstract Background Underserved and underrepresented populations often lack access to affordable, quality healthcare, educational resources, and nutritious foods, all of which contribute to increased risk of Type 2 Diabetes and gout. Type 2 Diabetes is a condition characterized by the denaturation of the insulin receptors, due to chronically high blood glucose levels, leading to impaired regulation of blood sugar. Gout is a chronic inflammatory disease affecting joints in the lower limbs, marked by elevated serum urate levels and the accumulation of uric acid crystals in synovial fluid, causing painful flare-ups that significantly impact quality of life. Methods This multisite cross-sectional study was conducted in three low-income senior residential communities across the mid-Atlantic United States, including Philadelphia and Harrisburg, Pennsylvania, and Clinton, Maryland. A total of 88 consenting participants were surveyed on their health history and tested for hemoglobin A1c (HbA1c), blood glucose, and uric acid levels using finger-stick blood tests and commercially available devices. Inclusion criteria included individuals of any gender, aged 35–92, residing in these communities. Exclusion criteria were a personal history of cancer, organ transplantation, or current pregnancy. Educational materials were provided after discussing each participant’s results. Results There is an identifiable prevalence of gout among this population of low-income senior adults living with Type 2 Diabetes. Among the participants, 30.7% had serum urate levels indicative of hyperuricemia, exceeding the national average of 20.1% as reported by the National Health and Nutrition Examination Survey. Participants with high HbA1c had significantly higher uric acid levels compared to those with lower HbA1c levels, with diabetic levels of HbA1c accounting for approximately 40% of the variance in uric acid levels. Additionally, study participants who smoked cigarettes were more likely to have hyperuricemia than non-smokers. Conclusion Preventive educational efforts focused on diet and lifestyle are critical to reducing the incidence of gout and Type 2 Diabetes in low-income elderly populations. Diabetic individuals are at a higher risk of developing hyperuricemia and gout compared to non-diabetics. Community-based educational health programs are necessary to make a measurable impact on these populations, prevent disease progression, and reduce the burden on healthcare systems.